Faktor yang Menghambat Pembelajaran Daring Pada Mahasiswa Bimbingan dan Konseling Universitas PGRI Semarang - Nurul Alimah (Dharmas Education Journal (DE_Journal), 2021)
This research was motivated by the covid-19 pandemic which gave rise to various problems, especially the economy in Indonesia was deteriorating and also resulted in the education system so to decide the spread of covid-19 distance learning was implemented so that students were required to carry out online learning. The problem revealed in this research is to get an idea of ​​how the inhibiting factors of online learning in Guidance and Counseling students at PGRI University Semarang. The goal to be achieved in this research is the inhibiting factor of online learning in students during online learning whether it is able to bring up positive behavior or even bring up negative behavior. This type of research is a qualitative research with case study method. Respondents in this study were guidance and counseling students as many as 3 students and 3 lecturers. The data in this study were obtained through interviews, observation and documentation. Based on the results of the analysis of research data, it shows that the inhibiting factors for online learning of students with other students are different, overall in the inhibiting factors of online learning the highest percentage is self-ability, facilities, and the environment. Subjects who are able to manage inhibiting factors of online learning well will be able to show positive behavioral changes in the learning process while subjects who have not been able to manage barriers to online learning show negative behavior changes in the learning process.